Kajian Literatur tentang Pemanfaatan Tanaman Air dalam Bioremediasi Limbah Amonia pada Akuakultur - Bhersiani Kirana Pangestu; Putri Hawa; Philipus Uli Basa Hutabarat; Endang Hilmi; Nuning Vita Hidayati (Biocaster : Jurnal Kajian Biologi, 2026)
The aim of this study is to synthesise the findings of various studies on the effectiveness of aquatic plants in reducing ammonia concentrations in aquaculture systems, to identify the mechanisms of phytoremediation involved, and to compare the effectiveness of different plant species based on previous studies. The method used was a systematic literature review with a descriptive-qualitative approach. This study did not conduct experiments or collect primary data, but rather used secondary data from relevant scientific articles. Literature was obtained from Google Scholar, ScienceDirect, and other indexed journals using keywords related to ammonia, aquaculture, phytoremediation, and water plants. The inclusion criteria included original research articles from 2015–2026 that were available in full text and presented quantitative data on ammonia reduction. Fifteen articles that met the criteria were analysed using thematic synthesis through grouping, comparison, and interpretation of data. The results of the synthesis showed that floating water plants such as Eichhornia crassipes, Pistia stratiotes and Lemna minor were the most effective, with ammonia reduction of over 90% in several studies. The main mechanisms include nitrogen absorption by the plants, rhizofiltration, and microbial activity through nitrification in the root zone. The effectiveness is influenced by biomass, root systems, and environmental conditions such as pH, temperature, and nutrient concentration. In conclusion, the synthesis of various studies shows that phytoremediation based on floating aquatic plants is effective and has the potential to be a sustainable and environmentally friendly technology for the treatment of aquaculture waste.